PENGARUH PENDIDIKAN KARAKTER TERHADAP BERPIKIR KRITIS SISWA DI ERA MASA KINI - Desty Endrawati Subroto; Ratih Cahniyati Putri; Windi Novianti; Selviyana Putri; Nafalie Cheisya Dermawan (CV. Denasya Smart Publisher, 2025)
This research aims to analyze the relationship between character education and the Z generation’s critical thinking skills in order to become intelligent and characterful individuals to compete globally. This research uses literature analysis methods. The results show that character education involves three main aspects, namely understanding good values, loving good values, and applying good values. Character education is an important element in forming individuals with integrity and noble character. In the digital era, the influence of social media, wide access to information and technology emphasizes the need for more relevant character education. This research examines the role of character education, the challenges faced, and strategies for overcoming them through a holistic approach involving families and society with wise use of technology.